Treatment of multiple recession defects with vestibular incision subperiosteal tunnel access (VISTA): A retrospective pilot study utilizing digital analysis. Issue 6 (27th October 2018) - Gil, Alfonso; Bakhshalian, Neema; Min, Seiko; Zadeh, Homayoun H.
Abstract: Objective: To examine the correlation between initial site‐specific characteristics of patients with multiple gingival recession defects and the outcome of root coverage therapy. Materials and Methods: Pretherapy and post‐therapy study models of 21 patients (154 teeth) with multiple gingival recession defects, treated with Vestibular Incision Subperiosteal Tunnel Access (VISTA), were optically scanned. Three‐dimensional analysis of superimposed preoperative and postoperative images was performed. Linear and surface root coverage were calculated and correlated to various clinical and/or anatomical parameters. A multilevel statistical analysis was conducted, adjusting for the correlation among multiple observations. Results: The mean percentages of linear root coverage were 96.2 ± 13.1% and 84.3 ± 14.4% for Miller Class I/II and Class III recessions, respectively. The mean percentages of root surface area coverage were 92.1 ± 12.0% and 78.6 ± 15.7% for Miller Class I/II and III defects, respectively. Root prominence, initial recession width and posterior tooth type were negatively correlated with linear and root surface area coverage. Initial recession depth was negatively correlated with root surface area coverage. Initial gingival margin thickness was positively associated with both linear and root surface area coverage. Conclusion: The results of the present study identified important positive and negative site‐specific characteristics that may have utility in predicting the outcome of root coverage. Clinical Significance: This study used sensitive 3‐dimensional digital analysis tools to examine the correlation between initial site‐specific characteristics of patients with multiple gingival recession defects and the outcome of periodontal root coverage therapy. Results demonstrated that initial root prominence, loss of interdental tissue (Miller Class III), molar tooth type, initial recession depth and width were negatively correlated with the outcome of periodontal root coverage achieved. Conversely, initial gingival margin thickness was associated with increased percentage of root coverage. These site‐specific characteristics may serve as important risk indicators to predict the outcome of root coverage procedure.